Desvelando a construção das diferenças de gênero nas experiências de contadores/as e de auditores independentes em Sergipe - Pinto, Mariana Dórea Figueiredo (2017)
In recent years, a significant transformation of Accounting has been its increasing feminization. If in 2006 women's participation in this profession was 39%, currently it has been 46% of the universe of active professionals, registered in the Brazilian Federal Accounting Council. The tendency is that it increases, since the female universe already corresponds to 60% of the entrance in Accounting graduation courses. However, in the Independent Auditing, a specialization of the accounting profession that demands a differentiated qualification, women correspond only to 20% of the professionals in this area and, in the state of Sergipe, Brazil, there is no representation. Independent Auditing may be considered to be a specialty of accounting dominated by men. In this sense, the approach of work and gender in the field of accounting, from the post-structuralist and constructivist perspectives, allows us to identify the dimension of career feminization without, however, disregarding its historical process or the pace that changes occurred in several professions recently. Thus, this thesis aims to analyze, from the perspective of gender, the insertion, rise and permanence in the work of accountants and independent auditors in the State of Sergipe, Brazil, and how they attribute meanings and purpose to work, training processes and qualification. The methodology was organized in a qualitative and quantitative manner, through semi-structured interviews with 19 professionals, of which 09 were independent auditors with the National Registry of Independent Auditors (CNAI in Portuguese), approved in the Technical Qualification Examination (TEQ), and 10 accountants, of which 03 are in the leadership of the class representations of the State. The analytical and interpretative process was developed based on Content Analysis (CA) and the results show that even with the feminization of accounting and with a higher level of qualification in relation to the male professional, the sexual division of labor is still present in women accountants’ professional and personal trajectories. Discussing gender relations in the Accounting and Independent Auditing jobs is essential when thinking about a democratic society that enables men and women to have equal opportunities and working conditions.________________________________________________________________________________________________________________________________